Effect of Differences in Temperature and Storage Time on The Number of Microbes in Fresh Lemuru Fish (Sardinella lemuru) - Nandya Fitri Rachmawati; Siti Tsaniyatul Miratis Sulthoniyah (International Journal of Marine Engineering Innovation and Research, 2022)
Lemuru fish is a pelagic fish that is widely found in Indonesian waters that have an economical selling price. Fish is a food that is easily damaged so it requires good and correct handling. The purpose of this study was to determine the effect of temperature and storage time on the number of microbes in fresh lemuru fish. This study uses a quantitative research design. The treatment in this study was carried out with 2 treatments of differences in temperature and time. The number of microbes obtained at 00C at storage time for 0 hours (10,1 x 104 colonies / ml), 24 hours (8,8 x 104 colonies / ml), and 48 hours (6,3 x 104 colonies/ml). At 50C at storage time for 0 hours (10,2 x 104 colonies/ml), 24 hours (9,8 x 104 colonies/ml), and 48 hours (9,0 x 104 colonies/ml). At 270C at storage time for 0 hours (10,4 x 104 colonies/ml), 24 hours (23,3 x 104 colonies/ml), and 48 hours (29,8 x 104 colonies/ml). In conclusion, the longer the storage time of lemuru fish with low temperatures, the number of microbes that grow is small.